Proceedings of the 4th International Conference on Sustainable Innovation 2020-Accounting and Management (ICoSIAMS 2020) 2021
DOI: 10.2991/aer.k.210121.020
|View full text |Cite
|
Sign up to set email alerts
|

How Store Environment and Sales Promotion Influence Positive Emotions and Unplanned Purchases

Abstract: This study investigates how store environments and sales promotion affect positive emotions and unplanned purchases. Store environment and sales promotion are the independent variables that affect positive emotions as the mediating one. The predictor variable is unplanned purchases. The setting of the study is a global hypermarket. The sample size is 159 respondents, selected by using the purposive sampling method. The data analysis technique utilized in this research was Structural Equation Modeling (SEM), wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…This indicates that on these criteria female respondents feel more positive emotions (positive emotion) when they are in retail store X in Malang City because female consumers feel a good and comfortable store atmosphere caused by supporting store environment factors such as neat product layout, good lighting, service friendly saleswoman, making consumers feel at home lingering in the store. These results are in line with research from [13][14][15].…”
Section: The Effect Of the Store Environment On Positive Emotionsupporting
confidence: 92%
See 2 more Smart Citations
“…This indicates that on these criteria female respondents feel more positive emotions (positive emotion) when they are in retail store X in Malang City because female consumers feel a good and comfortable store atmosphere caused by supporting store environment factors such as neat product layout, good lighting, service friendly saleswoman, making consumers feel at home lingering in the store. These results are in line with research from [13][14][15].…”
Section: The Effect Of the Store Environment On Positive Emotionsupporting
confidence: 92%
“…This proves that the higher the level of the store environment can increase impulse buying. This is in line with research from [13] and [18] which states that store nuances created by store owners to provide information to consumers and create feelings and emotions to increase the opportunity for purchase by consumers in their stores. It can be concluded that the X retail store in Malang City also regulates the atmosphere of the store environment as comfortable as possible and in accordance with the concept of the target market, namely people who come to shopping centers to do windows shopping to feel at home and linger in the store and can cause positive consumer emotions in shopping.…”
Section: The Effect Of the Store Environment On Positive Emotionsupporting
confidence: 85%
See 1 more Smart Citation